The relationship of family functionality and parent behavior on adolescent delinquent behavior - Syahira Yusoff; Kamarul Md Shah; Nor Shakirah Mohd Sakari; Nur Sufia Suhail Ahmad (Intelektual Pustaka Media Utama, 2022)
Adolescent social problems involving juvenile delinquents concentrate around factor such as family functionality and parental behavior. The purpose of this study was to determine the relationship of family functionality and parent behavior on adolescent delinquent behavior. This study included 196 female delinquent adolescent inmates from four Malaysian correctional and rehabilitation centers in Malaysia. Data was collected using a questionnaire set that included background characteristics, The Family Adaptability and Cohesion Evaluation Scale (FACES) IV, The parental behavior inventory (PBI), and Inventory Delinquency Scale. The descriptive statistics and Pearson correlation were used to analyses the data. The result showed that family functionality has a significant association with delinquent behavior (r=-.255, p<001). Parental behavior also has a significant association with juvenile delinquent behavior (r=.411, p<.001).